Prevalence of human papillomavirus genotypes and related cervical morphological results in southern Hunan Province of China, 2018–2020: Baseline measures at a tertiary institution prior to mass human papillomavirus vaccination - Lan, Zhihua; Zhang, Jing; Li, Hongtao; He, Rongfang; Zhao, Qiang; Yang, Fang (Frontiers in Microbiology, 2023)
Background: Human papillomavirus (HPV) infection is closely correlated with cervical lesions. However, the HPV prevalence varies among different districts. This retrospective study investigated the HPV genotype distribution and its relationship with cervical lesions in southern Hunan Province. Methods: The database at our Pathology Department was searched for HPV and morphological results during 2018-2020 were reviewed. A total of 49,955 gynaecological inpatients and outpatients, each of whom underwent HPV testing based on the amplification of L1 sequence and reverse dot blot hybridization, were included in this study. Available cytology and relevant histological examination results were reviewed. Enrolled cases were categorized into seven groups based on their age. Results: 7286 females were positive for HPV and the overall HPV positivity rate was 14.59%. The top five most prevalent HPV genotypes were HPV52, 16, 58, 53 and 51 (22.98%, 17.54%, 14.29%, 7.47%, and 5.70%, respectively). The HPV prevalence curve specific to the seven age groups showed a bimodal distribution. High school education or blow and rural residence served as risk factors for HPV infection. Single infection was the main type of HPV infection, and multiple infections occurred in 21.92% (95%CI,20.98-22.89%) of the infected women. Of 3148 cases had cytological results, 1149 had abnormal cytological abnormalities. Among 2833 participants with histological examination,2000 had cervical abnormalities. Cytological and pathological abnormalities were mainly associated with infection with HPV16, 52 and 58. Further analysis found that HPV16, 58, 52 and 33 were the main genotypes associated with high-grade squamous lesions (HSIL) and that HPV16, 31, 33 and 58 were independent risk factors for HSIL (odd ratio [OR]= 1.70,1.99,2.59,2.29; 95%CI= 1.41-2.03, 1.17-3.41, 1.88-3.59,1.85-2.82; all P<0.05). HPV16, 58, 52, 18 and 33 were the most frequent genotypes detected in squamous cell carcinoma (SCC) patients, and HPV16 and 18 were independent risk factors for cervical carcinomas (OR=6.72;95% CI=5.48-8.25; P<0.001; OR=1.67, 95% CI=1.22-2.30; P=0.001). Conclusion: This retrospective study demonstrated the prevalence and the distribution characteristics of HPV infection and its correlation with cervical lesions in southern Hunan Province. The comprehensive results of this survey can guide HPV vaccine research to protect against some common genotypes in China.